Sodium/calcium exchanger as main effector of endogenous neuroprotection elicited by ischemic tolerance. (May 2020) - Pignataro, G.; Brancaccio, P.; Laudati, G.; Valsecchi, V.; Anzilotti, S.; Casamassa, A; Cuomo, O.; Vinciguerra, A.
Highlights: NCX takes part to the protection induced by brain conditioning. Preconditioning-induced factors able to activate NCX include transcription factors such as HIF1a, REST, SP1/SP3, DREAM. Survival factors, such as ERK and AKT contribute to NCX activation after preconditioning. NCX post-translational modificators, such as sumoylation, contribute to preconditioning-induced protection. Proteins contributing to Ca2+ homeostasis such as ORAi/STIM cooperate with NCX in mediating protection. Abstract: The ischemic tolerance (IT) paradigm represents a fundamental cell response to certain types or injury able to render an organ more "tolerant" to a subsequent, stronger, insult. During the 16th century, the toxicologist Paracelsus described for the first time the possibility that a noxious event might determine a state of tolerance. This finding was summarized in one of his most important mentions: " The dose makes the poison ". In more recent years, ischemic tolerance in the brain was first described in 1991, when it was demonstrated by Kirino and collaborators that two minutes of subthreshold brain ischemia in gerbils produced tolerance against global brain ischemia. Based on the time in which the conditioning stimulus is applied, it is possible to define preconditioning, perconditioning and postconditioning, when the subthreshold insult is applied before, during or after the ischemic event, respectively. Furthermore, depending on the temporal delay from the ischemic event, two different modalities are distinguished: rapid or delayed preconditioning and postconditioning. Finally, the circumstance in which the conditioning stimulus is applied on an organ distant from the brain is referred as remote conditioning . Over the years the " conditioning " paradigm has been applied to several brain disorders and a number of molecular mechanisms taking part to these protective processes have been described. The mechanisms are usually classified in three distinct categories identified as triggers, mediators and effectors . As concerns the putative effectors, it has been hypothesized that brain cells appear to have the ability to adapt to hypoxia by reducing their energy demand through modulation of ion channels and transporters, which delays anoxic depolarization. The purpose of the present review is to summarize the role played by plasmamembrane proteins able to control ionic homeostasis in mediating protection elicited by brain conditioning, particular attention will be deserved to the role played by Na + /Ca 2+ exchanger .